Pendekatan Hermeneutika Mutawalli Asy-Sya’rawi: Telaah Hadis Tentang Allah al-Rahma>n dalam Kitab al-Aha>di>s al-Qudsiyah - aco, Ahmad amri ahsani; Muhid (Universitas Islam Negeri Alauddin, 2025)
This research discusses hermeneutics, a discipline concerned with approaches to understanding complex texts, particularly those of the ḥadīth and the Qur’ān. In the context of this study, hermeneutics is employed as a theoretical framework to explore the interpretation of ḥadīth using both textual and contextual approaches, which are essential foundational concepts. The textual approach focuses on direct analysis of the ḥadīth text itself, while the contextual approach emphasizes the importance of understanding the social, cultural, and historical contexts that inform and influence the meaning of the ḥadīth. The methodology used in this research is qualitative, employing a literature review as the primary method, supported by analytical interpretation and reconstruction of related texts. In examining the Qudsī ḥadīth concerning Allah al-Raḥmān found in al-Aḥādīth al-Qudsiyyah by Shaykh Muḥammad Mutawallī al-Shaʿrāwī, this study applies a hermeneutical method, particularly the approach of tafsīr bi al-raʾy (interpretation based on reasoned opinion). This method is considered effective in uncovering and explaining the inner dimensions and spiritual meanings of the ḥadīth. The literature-based investigation revealed several parallels between this hermeneutical approach and interpretive methods employed in other scientific disciplines, indicating the interdisciplinary potential of hermeneutics in ḥadīth studies. Consequently, a comprehensive understanding of hermeneutics as applied to the interpretation of ḥadīth requires not only a close and detailed textual analysis but also a deep engagement with the socio-cultural and historical frameworks that shaped the emergence and reception of these traditions.